2023
DOI: 10.3390/mi14050988
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Preparation Temperature on the Different Facets of Bulk MgB2 Superconductors

Abstract: Two MgB2 samples were prepared using the spark plasma sintering (SPS) technique at different temperatures—950 °C (S1) and 975 °C (S2)—for 2 h under 50 MPa pressure to study the influence of preparation temperature on different facets, namely those perpendicular (PeF) and parallel (PaF) to the compression direction of uniaxial pressure during the SPS of MgB2 samples. We analyzed the superconducting properties of the PeF and PaF of two MgB2 samples prepared at different temperatures from the curves of the critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, PIT MgB 2 wires have several disadvantages, such as a large number of voids, poor connections between grains, low density of pinning centers, low irreversible magnetic field, and large grains [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Current research has shown that doping allows for increasing the density of pinning centers [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, PIT MgB 2 wires have several disadvantages, such as a large number of voids, poor connections between grains, low density of pinning centers, low irreversible magnetic field, and large grains [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Current research has shown that doping allows for increasing the density of pinning centers [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%